2019 11th Computer Science and Electronic Engineering (CEEC) 2019
DOI: 10.1109/ceec47804.2019.8974311
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Occupancy Monitoring Unit: A Thermal Imaging Based People Counting Solution for Socio-Technical Energy Saving Systems in Hospitals

Abstract: Aside from their physical exterior/interior design, the energy demands of industrial buildings are strongly related to how they are used. It follows that the behaviour of the occupants contributes and is related to the energy consumption of a building. In a hospital, this could mean equipment usage, heating, water and so on. This implies that energy consumption in a specific area may be measured as a function of occupancy, making occupancy monitoring an important part of an organisation's energy management pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The advantage of this was the easy and rapid access to anonymous occupancy figures crucial for the timely progression of the study. Other techniques of people counting involve using technologies such as radio frequency identification (RFID) [55], Wi-Fi [56], and thermal imaging [57]. Although, deploying such technologies in a hospital environment can face several challenges, due to privacy (such as with RFID) and compliance with the health code; those approaches can be considered for future research.…”
Section: Electricity Consumption and Occupancy Datamentioning
confidence: 99%
“…The advantage of this was the easy and rapid access to anonymous occupancy figures crucial for the timely progression of the study. Other techniques of people counting involve using technologies such as radio frequency identification (RFID) [55], Wi-Fi [56], and thermal imaging [57]. Although, deploying such technologies in a hospital environment can face several challenges, due to privacy (such as with RFID) and compliance with the health code; those approaches can be considered for future research.…”
Section: Electricity Consumption and Occupancy Datamentioning
confidence: 99%
“…Presence and activity detection systems can play a vital role in this and can complement Internet of Things (IoT) use cases for smart cities, such as the wireless electricity data logger introduced in 5 , to control in-home energy consuming systems such as lights, appliances, and so on.Several studies in the literature have discussed and evidenced the relationship between building occupancy and energy consumption. For instance, a study was reported in 6 showing that forecasted energy consumption can be skewed by up to 300% if occupancy was not accounted for. Another study 7 confirmed this by showing that actual consumption could be up to three times greater than the simulation and one of the factors contributing to this big gap is occupants' behaviour and their numbers 8,9 .…”
mentioning
confidence: 99%
“…Several studies in the literature have discussed and evidenced the relationship between building occupancy and energy consumption. For instance, a study was reported in 6 showing that forecasted energy consumption can be skewed by up to 300% if occupancy was not accounted for. Another study 7 confirmed this by showing that actual consumption could be up to three times greater than the simulation and one of the factors contributing to this big gap is occupants' behaviour and their numbers 8,9 .…”
mentioning
confidence: 99%